Analysis of Rural Women’s Participation in Rice Production using Ordinal Logistic Regression Model - Adugna, Almaz Giziew; Gessesse, Mekuria Yimer (Journal of Rural Development, 2019)
This research was carried out in Fogera district, located in South Gondar Administrative zone, Ethiopia in 2014/2015 production year. In the area, rice is one of the means of livelihood. The objective of the research was to identify the determinants of the level of rural women participation in rice production. Among the 24 rice producing kebeles, four kebeles were selected following simple random sampling technique. Respondents were stratified into women in female and male headed households. Primary quantitative data was collected through household survey. The data were analysed using descriptive statistics such as mean Std. Dev, pair-wise ranking, percentage distribution, F-test and chi-square test. Women’s participation was analysed by participation index, and further was categorised into high, medium and low. The ordinal logistic regression model was used to estimate the effects of hypothesised explanatory variables. The results of the econometric model indicated women categorisation, farm size, on-farm income, offfarm income, farm nearness to development centre and rice production training. Based on the findings of the research, capacitating women through training and introduction of cost and burden of women reducing technologies are recommended.